FDI, liquidity, and political uncertainty: A global analysis - Marvin Jahn; Paul Stricker (International Economics and Economic Policy, 2022)
Uncertainty incentivizes investors to wait-and-see and to hold back their investments. This paper investigates whether more liquid types of foreign direct investment (FDI) are affected more by political uncertainty than less liquid ones. Drawing from the real options theory, we develop hypotheses on the sensitivity of different types of FDI. We utilize descriptive statistics and a simple estimation approach to gauge the liquidity of quarterly equity investments, reinvested earnings, and intra-company debt. Then, we deploy election data and the World Uncertainty Index to examine how the three FDI subtypes respond to high political uncertainty. In line with the real options theory, reinvested earnings significantly drop in an election quarter. However, this only holds for high-income countries. In lower-middle- and low-income countries, electoral uncertainty negatively affects equity investments, with higher institutional quality moderating the effect. In particular, the number of veto players and the government's credibility decrease the effect of uncertainty on FDI.
Keywords: F21; F23; G18; 330; Foreign direct investment; Political uncertainty; Reinvested earnings; Equity; Multinational enterprises